Association between Air Pollutants and the Risk of Sleep Disorders: A Systematic Review and Meta-analysis - Yizhuo Zhao; Suo Zhang; Liqiong Guo; Meng Xiao; Zhuo Han; Yuewei Yang; Bo Wang; Penghui Li (Aerosol and Air Quality Research)
Abstract Background Sleep disorders have become prevalent, but the association between air pollutants and the risk of sleep disorders remains unclear. In this study, a meta-analysis was carried out to examine this relationship. Methods A systematic review and meta-analysis for publications from January 1, 2000 to February 1, 2023 was conducted to clarify the association between air pollutants and the risk of sleep disorders. Results We identified 18027 articles from ScienceDirect, Web of Science, PubMed, and Embase, and 10 met our inclusion criteria. The results suggested that there were significant positive associations between PM2.5, PM10, NO2 exposure and sleep disorders (for each 10 µg m−3 increment of PM2.5, PM10, and NO2, OR: 2.50, 95% CI: 1.87–3.32; OR: 1.15, 95% CI: 1.06–1.24; OR: 1.36; 95% CI: 1.17–1.59, respectively). Conclusions Exposure to PM2.5, PM10, and NO2 can lead to an increased risk of sleep disorders. Further studies with other pollutants are needed to clarify the association between air pollutants and sleep disorders.